ICT for assessment and rehabilitation in Alzheimer's disease and related disorders - Philippe Robert (Frontiers Research Topics, 2016)
Information and Communication Technologies (ICT) are no longer objects gathering dust on a shelf; instead, they have become intrinsic in our everyday lives. They are now even taking on an indispensable role in many clinical and rehabilitation settings. In the past decade there has been a surge of interest in using ICT with elderly people, both with and without dementia, in various clinical and research settings. On the one hand, ICT can supplement the assessment of functional ability by more precisely evaluating the nature and extent of functional impairment; on the other hand, ICT can be used to support elderly people in their everyday activities, as well as to ameliorate symptoms and improve quality of life through stimulation and rehabilitation. This is the intention driving the development of Serious Games (SG), which are digital applications (often based on Virtual Reality) specifically adapted for purposes other than entertaining, including rehabilitation, training and education. Finally, ICT can also play a key role in the development of interactive educational programs to support caregivers of people living with dementia. A handful of interesting studies have started to investigate the effectiveness of employing ICT in people with different types of dementia, such as Alzheimer's disease (AD). It is therefore timely to attempt to scope this newly emerging field, as well as to foster a dialogue among the different professionals, including academics, clinicians and computer engineers, working in the area. With this in mind, the Research Topic "ICT for assessment and rehabilitation in Alzheimer's disease and related disorders" aims to provide new and interesting insights into the current use of ICT in healthy and pathological aging. The intent is also to identify challenges and new perspectives in the field, gather recommendations for the application of ICT in AD and related disorders in clinical practice, and to showcase cutting edge clinical research. The articles included in this Frontier Research Topics have more than achieved this aim and are a perfect illustration of how ICT can be used to enhance the lives of people living dementia and their caregivers.